Benzotriazole-containing donor–acceptor–acceptor type cyclometalated iridium(III) complex for solution-processed near-infrared polymer light emitting diodes. (August 2016) - Yu, Junting; Tan, Hua; Meng, Fanyuan; Lv, Kun; Zhu, Weiguo; Su, Shijian
Abstract: A novel near-infrared-emitting cyclometalated iridium(III) complex of (CH3 OTPA-BTz-Iq)2 Irpic containing benzotriazole unit with a donor–acceptor–acceptor (D-A-A) chromophore was synthesized and characterized. The optophysical, electrochemical and electroluminescent characteristics were primarily studied. A near-infrared emission peaked at 716 nm with a shoulder at 790 nm was exhibited in the (CH3 OTPA-BTz-Iq)2 Irpic dichloromethane solution at 298 K. In its optimized solution-processed polymer light-emitting diodes, a near-infrared electroluminescent emission peaked at 723 nm with a shoulder at 780 nm was observed with a maximum external quantum efficiency of 0.41% at 8.14 mA cm −2 . This work indicates that introducing appropriate D and A units to develop D-A-A structure is an efficient approach to construct near-infrared-emitting iridium(III) complex in the polymer light-emitting diodes with suppressive efficiency roll-off. Graphical abstract: A novel benzotriazole-containing donor-acceptor-acceptor type cyclometalated iridium(III) complex of (CH3 OTPA-BTz-Iq)2 Irpic was synthesized. Using it as a dopant and a blend of PVK and OXD-7 as a host matrix, the PLEDs exhibited a near-infrared (NIR) emission peaked at 723 nm and a shoulder at 780 nm with the maximum EQE of 0.41% at 8.14 mA cm −2 . This work indicates that introducing appropriate D and A unit to develop D-A-A structure is an efficient approach to construct near-infrared-emitting iridium(III) complex and obtain high-efficiency near-infrared polymer light-emitting diodes with suppressive efficiency roll-off. Highlights: A novel iridium(III) complex of (CH3 OTPA-BTz-Iq)2 Irpic with a D-A-A structure was synthesized. The (CH3 OTPA-BTz-Iq)2 Irpic shows an emission at 718 nm and a shoulder at 790 nm in solution at 298 K. The (CH3 OTPA-BTz-Iq)2 Irpic-doped PLEDs exhibited a near-infrared EL emission peaked at 723 nm. The maximum EQE of 0.41% and a radiant intensity of 74.1 μW cm −2 were obtained in their doped PLEDs.